Completion for a Geometric-Function Problem: Process and Resources in Efficiency Consideration - Fiki Alghadari; Bayu Jaya Tama; Sudirman Sudirman; Arie Purwa Kusuma; Syafa'at Ariful Huda (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
The cognitive level between teachers and students is clearly different in problem-solving. In the mathematics context, especially the function problem was only in geometric expression form, for knowledge construction and student's learning should use their cognitive level capacity. Not only the solving process is based on that, but also learning should be efficient for all students, and analyzing those processes is the purpose of identification inefficient issues in this study. This investigative study was held on three respondents purposively selected from a science program of senior high school in West Jakarta, Indonesia. This study found that in the solving process, all students chose to construct an algebraic representation of the function by organizing concepts relevant to fragmented conceptualization. The process has held to apply each concept procedurally. There has been a resource and that is one concept of the domain of function, so the completion is an inefficient process because all three students were ignoring it to use. All three process for solving to the student’s academic culture, most common for emphasizing in learning related to the problem and their cognitive capacity.